Kekuatan Hukum Surat Keterangan Pernyataan Ganti Rugi Yang Dikeluarkan Kecamatan Medan Helvetia Sebagai Informasi Pertanahan - Saragih, Dikki Saputra; Micael Jeriko Damanik (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
In this research, it is explained that legal subjects must have legal land ownership in accordance with the actual situation. The issues to be discussed are the juridical analysis of land ownership as proven by a correct statement of compensation by the Medan Helvetia District, legal force in terms of letters issued by the sub-district office, and the legal impact on legal subjects that do not change the statement of compensation. loss by the District. In terms of discussion, the juridical analysis of land ownership as evidenced by a certificate of compensation statement by the Medan Helvetia District as a Temporary PPAT is to ensure correct land registration. Regarding the legal force in the case of a letter issued by the sub-district office which is valid because it takes into account the interests of the parties making the land sale and purchase and is accompanied by a receipt signed by the parties, regarding the legal impact on legal subjects that do not change or crosscheck the land certificate must be forcibly carry out crosschecks so that no one suffers losses.